2021
DOI: 10.3389/fimmu.2021.723196
|View full text |Cite
|
Sign up to set email alerts
|

HCV Cure With Direct-Acting Antivirals Improves Liver and Immunological Markers in HIV/HCV-Coinfected Patients

Abstract: Hepatitis C virus (HCV) cure after all-oral direct-acting antiviral (DAA) therapy greatly improves the liver and immune system. We aimed to assess the impact of this HCV clearance on immune system-related markers in plasma and the gene expression profile in human immunodeficiency virus (HIV)/HCV-coinfected patients with advanced cirrhosis. We performed a prospective study on 33 HIV/HCV-coinfected patients at baseline and 36 weeks after the sustained virological response. Gene expression was evaluated by RNA-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 98 publications
2
14
0
Order By: Relevance
“…Brochado-Kith et al showed that following DAA therapy in HCV/HIV co-infected patients (n = 33) at 36 weeks after SVR, patients with advanced cirrhosis had an improvement in liver disease markers and a significant decrease in plasma biomarkers and gene expression related to antiviral/inflammatory response, particularly in levels of several chemokines and ISGs. However, normalization of the biomarker values was not achieved, as observed by comparison with HCV (n = 9) and HIV (n = 26) mono-infected patients [17].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Brochado-Kith et al showed that following DAA therapy in HCV/HIV co-infected patients (n = 33) at 36 weeks after SVR, patients with advanced cirrhosis had an improvement in liver disease markers and a significant decrease in plasma biomarkers and gene expression related to antiviral/inflammatory response, particularly in levels of several chemokines and ISGs. However, normalization of the biomarker values was not achieved, as observed by comparison with HCV (n = 9) and HIV (n = 26) mono-infected patients [17].…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, a larger study reported a reduction in total activated (HLA-DR+ and CD38+) CD4+ and CD8+ T cells in both groups of patients one-year post SVR [16]. A more recent study showed a significant decrease in plasma biomarkers and gene expression related to antiviral/inflammatory response, particularly in levels of several chemokines and ISGs in HCV/HIV-co-infected patients; however, complete normalization of the immune system was not achieved, as observed by comparison with HCV and HIV mono-infected patients [17]. The studies mentioned above evaluated the effects of treat-ments on T-cell activation and immune system-related plasma biomarkers at SVR or for short time follow-up with discordant results.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The introduction of direct-acting antiviral agents (DAAs) against HCV has significantly improved the prognosis of HCV/HIV co-infected patients undergoing liver transplantation for end stage liver disease (ESLD) [ 7 , 8 , 9 , 10 , 11 ]. However, recent studies have suggested that DAA-mediated HCV eradication could represent an impediment to HIV reservoir elimination in coinfected patients [ 4 , 12 ], and that DAA treatment does not completely normalize immune and liver functions as well as the risk of hepatocellular carcinoma development [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%